(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: Events at sport-events are always unique, so they cannot be predicted with perfect certainty. However, risk analysis and accurate mapping of the circumstances can help to identify potential sources of danger and thus prepare for prevention, to prevent or eliminate illegal behaviour and to control its escalation. Methodology: Analysis of the available literature, legislative environment and statistical data, as well as participant observation of the practice of the Commission for the Safety Evaluation of Sport-events. Findings: The safety of sport-events has improved a lot in recent years due to the changing legislative environment, infrastructure investments, technical developments and last but not least the new security philosophy. However, in some areas, further improvements and a rethinking of the legislation seem advisable. These include more effective and rational enforcement of bans, exclusion, exclusion from and entry to sporting events, reform of the three-step security classification of sporting events, improvement of the activities of spotters (police liaison officers), more effective prevention of the illegal use of pyrotechnic articles and more effective action against racist manifestations. Value: The study aims to improve the safety of sport-events by emphasising the importance of risk analysis, taking into account practical experience.